The Evolution of Hydraulic Fracturing Technologies for the Carbonate Sediments of the Kashirsky and Podolsky Horizons of the Arlanskoe Oilfield - Ya. R. Islamov; E. R. Nurlygayanova; A. M. Vagizov; S. R. Nurov; R. F. Yakupov; A. K. Zaripov; M. R. Mukhametshin; M. V. Salimov (Georesursy, 2024)
This article reviews the evolution of hydraulic fracturing (HF) technologies for the carbonate sediments of the kashirsky and podolsky horizons of the Arlanskoe oilfield (the Republic of Bashkortostan and the Udmurt Republic) by the influence of changes in current development conditions, reserve depletion, clarification of the geological structure, and scientific and technical advancements. It presents an overview of the main technologies of primary hydraulic fracturing and re-fracturing actively used today and/or are being introduced on the industrial scale. For horizontal wells, hydraulic fracturing with hydraulic jet perforation (HJP) is employed. This technology enables the development of previously untapped or underperforming sections of the wellbore by allowing selective acid and proppant injection into specific intervals, offering high controllability and predictability. Both HJP and HF stages are completed in a single tripping operation without the need for a coiled tubing fleet. For directional wells, high-tonnage hydraulic fracturing with increased proppant mass up to 40–50 tons is a promising technological solution. This approach enhances to increase starting oil flow rates by improving coverage ratio due to involving poorly drained and previously undeveloped overlying and underlying layers. The article consolidates practical experience with hydraulic fracturing technologies, analyzes their effectiveness, identifies the features of hydraulic fracturing in directional and horizontal wells, and develops an algorithm for the selection of hydraulic fracturing technology for the conditions of a carbonate reservoir.